Application of ultrasonic pretreatment for drying of holy basil (Ocimum sanctum L.) leaves - D Khamon; J S Jongyingcharoen (My University, 2019)
This research aimed to study the effect of ultrasound (20 kHz) on the preparation of white holy basil leaves in the hot air drying process. Five pretreatments were applied, including 30-min ultrasonic, 60-min ultrasonic, blanching, steam blanching, and 30-min ultrasonic plus blanching pretreatments. From the study on drying characteristics of hot air drying of the pretreated samples at 60°C, the shortest drying time of 30 min was obtained when sequential ultrasonic and blanching pretreatment was conducted. All pretreatments could enhance the drying characteristics as the lowest drying time of 100 min was provided by hot air drying of unpretreated sample. Significant differences in the quality values of dried holy basil leaves subjected to different pretreatment were found. Blanching pretreatment resulted in minimum shrinkage of about 66%. The maximum rehydration ratio was 3.83 and found in the sample with 30-min ultrasonic plus blanching pretreatment. Dried holy basil leaves undergoing thermal pretreatments of blanching, steam blanching, and ultrasonic plus blanching led to were inclined to be darker and greener.
Keywords: Blanching; Shrinkage; Food Drying and Modeling